2019
DOI: 10.1002/hbm.24629
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and lateralized social brain activity for processing dynamic facial expressions

Abstract: Dynamic facial expressions of emotions constitute natural and powerful means of social communication in daily life. A number of previous neuroimaging studies have explored the neural mechanisms underlying the processing of dynamic facial expressions, and indicated the activation of certain social brain regions (e.g., the amygdala) during such tasks. However, the activated brain regions were inconsistent across studies, and their laterality was rarely evaluated. To investigate these issues, we measured brain ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 160 publications
(273 reference statements)
3
25
0
1
Order By: Relevance
“…In considering our results, it is worth noting that although we selectively targeted the left posterior cerebellum, in light of recent evidence suggesting a left hemispheric functional dominance in the cerebellum during the observation of dynamic emotional facial expressions (Sato et al, 2019), consistent activations have also been reported in the right posterior cerebellum during emotional processing (for a review, see Adamaszek et al, 2017). Accordingly, damage to the right posterior cerebellar regions may cause deficits in emotional discrimination (e.g.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In considering our results, it is worth noting that although we selectively targeted the left posterior cerebellum, in light of recent evidence suggesting a left hemispheric functional dominance in the cerebellum during the observation of dynamic emotional facial expressions (Sato et al, 2019), consistent activations have also been reported in the right posterior cerebellum during emotional processing (for a review, see Adamaszek et al, 2017). Accordingly, damage to the right posterior cerebellar regions may cause deficits in emotional discrimination (e.g.…”
Section: Discussionmentioning
confidence: 51%
“…To directly assess this issue, we examined the effect of transiently disrupting the activity of the left posterior cerebellum using 1 Hz repetitive TMS (rTMS) on the modulation of MEPs elicited from the primary motor cortex (M1) during the viewing of faces presenting a negative emotional expression. Although emotional processing drives activation in bilateral Crus I/II (Guell, Gabrieli, & Schmahmann, 2018;Keren-Happuch et al, 2014;Stoodley & Schmahmann, 2009), we specifically targeted the left cerebellum because recent findings indicate that there may be greater engagement of the left posterior cerebellum in response to emotional stimuli (Sato et al, 2019). Hence, participants first received 15 min of inhibitory 1 Hz rTMS (or a sham rTMS not intended to affect neural activity) over the left posterolateral cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…There are several other unique aspects of the neural processing of dynamic facial expressions compared with that of static expressions. For example, the observation of dynamic facial expressions evidently induces modulatory influences from the amygdala to the neocortex (Sato et al, 2017) and clearly reveals hemispheric functional asymmetry (right cortical and left cerebellar; Sato et al, 2019). Differences in the decoding of dynamic and static facial expressions have also been suggested by lesion studies (e.g., Humphreys et al, 1993).…”
Section: Decoding Of Dynamic Emotional Signalsmentioning
confidence: 90%
“…It has been shown that there is a right-dominant neuronal mechanism in FE processing. Furthermore, several studies related FE perception to widespread neuronal processing in the right hemisphere, with an organization similar to language processing in the left hemisphere [ 45 48 ]. Aside from pioneering functional magnetic resonance imaging (fMRI) studies on FE processing, there are also EEG studies demonstrating this hemispheric lateralization during FE processing [ 8 , 49 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from pioneering functional magnetic resonance imaging (fMRI) studies on FE processing, there are also EEG studies demonstrating this hemispheric lateralization during FE processing [ 8 , 49 52 ]. However, such results were obtained with stimulus sets that mostly used static photographs, where the temporal dynamics of face processing were not considered [ 45 , 46 , 53 ]. According to the valence hypothesis [ 49 , 50 , 54 ], increased left anterior activity is associated mostly with positive emotions, while increased right anterior activity is associated with negative emotions.…”
Section: Discussionmentioning
confidence: 99%